Short-term habituation of equine limb kinematics to tactile stimulation of the coronet - Clayton, H. M.; White, A. D.; Kaiser, L. J.; Nauwelaerts, S.; Lavagnino, M.; Stubbs, N. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
A lightweight bracelet that provides tactile stimulation to the horse’s pastern and coronet induces a higher flight arc of the hoof. This study addresses the pattern of habituation to these devices. Objective: To evaluate short-term habituation to tactile stimulation of the pastern and coronet in trotting horses. Methods: Tactile stimulation was provided by a lightweight (55 g) device consisting of a strap with seven chains that was attached loosely around the pastern. Reflective markers were fixed to the dorsal hoof wall, the forehead and over the tenth thoracic vertebra of eight sound horses. The horses trotted in hand 10 times at a consistent velocity along a 30 m runway under three conditions applied in random order at two-hour intervals: no stimulators, stimulators on both front hooves or stimulators on both hind hooves. One stride per trial was analyzed to determine peak hoof heights in the swing phase. Sequential trials with stimulators were compared with unstimulated trials using a nested ANCOVA and Bonferronni’s post hoc test (P<0.005). Results: Peak hind hoof height increased significantly for all 10 trials when wearing hind stimulators, whereas peak fore hoof height increased during the first six trials only when wearing fore stimulators. The first trial with stimulators showed the greatest elevation, followed by a rapid decrease over the next three trials and then a more gradual decrease. Conclusions: If the goal is to facilitate a generalized muscular response, a short burst of tactile stimulation is likely to be most effective, whereas longer periods of stimulation will be more effective for strength training.
Keywords: Horse; physical therapy; rehabilitation; proprioception; gait analysis